Determinant of functional disability in instrumental activities of daily living among elderly living in a rural area in Bali: a crosssectional study - Suyasa, I Gede Putu Darma; Sutini, Ni Kadek; Kamaryati, Ni Putu; Nuryanto, I Kadek (Universitas Airlangga, 2023)
Introduction: Little do we understand about factors associated with functional disability in instrumental activities of daily living among the elderly living at home. This study aimed to explore the prevalence and determinant factors of functional disability in instrumental activities of daily living (IADL) among the elderly living in a rural area in Bali. Method: Using a cross-sectional design, 1,053 elderly aged 60 years and above living in a rural area in Bali were recruited. A structured interview by trained data collectors was conducted. Questionnaires used were the Lawton IADL Scale, the 5-item of Geriatric Depression Scale, and the adoption of questionnaires for vision, hearing, and communication problems from the Washington Group Short Set of Questions on Disability. A logistic regression model was applied to explore determinant factors. Results: Findings indicated that 26.1% of participants aged 75+ and 52.3% were female. Eight percent (8%) experienced functional disability in IADL, 1.9% lived alone, 11.8% indicated depression, 5.1%, 4.7%, and 1.6% of them had vision loss, hearing impairment, and communication problems, respectively. The strongest determinant factor for functional disability in IADL was depression (OR 7.869; 95% CI 4.657-13.296), followed by age (OR 4.602; 95% CI 2.764-7.663), and hearing impairment (OR 2.903; 95% CI 1.190-7.083). Conclusions: Depression is the strongest determinant factor for functional disability in IADL. Health professionals in rural areas should actively screen for depression to increase the ability of the elderly to fulfill their IADLs. Keywords: aged, depression, epidemiology, Indonesia